PENGARUH TINGKAT KEPENTINGAN DAN PARTISIPASI MASYARAKAT TERHADAP EFEKTIVITAS PEMAHAMAN LAYANAN SISTEM ADMINISTRASI KENDARAAN PAJAK ONLINE (SAKPOLE) DI KOTA SEMARANG - Shinta Ayuningtyas, Tandria; Lituhayu, Dyah; Larasati Setianingsih, Endang (Journal of Public Policy and Management Review, 2024)
Taxes, including motor vehicle taxes, are crucial for national revenue and societal welfare. Local governments have the authority to manage taxes according to the law to support regional autonomy. Despite increasing numbers of vehicles, tax revenues remain suboptimal due to taxpayer non-compliance. The SAKPOLE application was introduced to facilitate online tax payments but faces technical challenges and low public understanding of technology. The aim of this research is to assess the Level of Interest and Participation of the Community Towards the Effectiveness of Understanding the Service of the Online Vehicle Tax Administration System (SAKPOLE) in Semarang City. The study used a sample of 100 respondents selected through simple random sampling. Data were collected via questionnaires and analyzed using validity and reliability tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination. The findings indicate that both partial and simultaneous levels of community interest and participation significantly influence the effectiveness of understanding the SAKPOLE service in Semarang City. Samsat Kota Semarang needs to enhance public participation in providing feedback on SAKPOLE services and ensure better transparency of information. The community should actively participate in SAKPOLE workshops and enhance their technological literacy. Future research should broaden the scope of study variables, use larger samples, and adopt diverse research methodologies to comprehensively understand SAKPOLE usage.